Pengaruh Serangan Penggerek Batang Padi terhadap Hasil Panen Tanaman Padi (Oryza Sativa L.) Di Subak Cemagi Let, Desa Cemagi, Kecamatan Mengwi, Kabupaten Badung - RAMADHAN, MOCH BINTANG; SUDIARTA, I PUTU; WIJAYA, I NYOMAN; SUMIARTHA, I KETUT (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Rice stem borer is one of the pests that can cause a decrease in rice yield. In Indonesia there are four types of rice stem borer namely S. incertulas, S. innotata, C. suppressalis and S. inferens. This study aims to determine the effect of rice stem borer attack on rice crop yields. The study was conducted for three months in February to April 2019 located in Subak Cemagi Let, Cemagi Village, Mengwi District, Badung Regency, using a diagonal sampling method, the effect of rice stem borer attack on yield reduction. Observations were made on the percentage of rice stem borer infestation, rice stem borer type, wet weight of rice plants. Observation test shows that rice stem borer attack changes every week and affects the rice crop yields.